2010
DOI: 10.1002/elan.201000079
|View full text |Cite
|
Sign up to set email alerts
|

Critical Effect of Polyelectrolytes on the Electrochemical Response of Dehydrogenases Entrapped in Sol‐Gel Thin Films

Abstract: The influence of polyelectrolyte (PE) additives on the sol-gel encapsulation of dehydrogenases has been evaluated using d-sorbitol dehydrogenase (DSDH) as a model enzyme. Thin sol-gel films were prepared on glassy carbon electrodes (GCE), which were then evaluated with respect to the electrochemical detection of d -sorbitol. DSDH encapsulation in pure silica thin films resulted in undetectable electrochemical signal. Adding positively-charged PE that contributes to stabilize the negatively-charged DSDH in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Again, no significant electrocatalytic response could be obtained. This result confirms the observation from previous investigations that the presence of positively charged polyelectrolyte (such as PEI) ensures suitable microenvironment for dehydrogenase encapsulation 10. This effect is mostly due to the stabilization of negatively charged dehydrogenase which in turn led to much faster and better response of GDH to its substrate.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Again, no significant electrocatalytic response could be obtained. This result confirms the observation from previous investigations that the presence of positively charged polyelectrolyte (such as PEI) ensures suitable microenvironment for dehydrogenase encapsulation 10. This effect is mostly due to the stabilization of negatively charged dehydrogenase which in turn led to much faster and better response of GDH to its substrate.…”
Section: Discussionsupporting
confidence: 90%
“…The entrapment of biomolecules in a silica sol‐gel matrix and their use in biosensing applications have also been developed in the past decade. Research works have shown that an enzyme can be durably immobilized by simple entrapment in porous gel networks without requiring any covalent bond between the support and the enzyme, thus maintaining its native properties and biological activity 710. In addition, when coated onto the electrode surface, the response time of the device can be greatly reduced by controlling the thickness of the silica layer 11.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of NADH, no enhanced current was observed (dashed line). Upon addition of 0.5 mM NADH a well-defined voltammetric peak can be observed at a potential of about + 0.4 V (solid line) which is about 300 mV lower than NADH oxidation at the bare GCE [18]. The electrocatalytic effect was even more pronounced after microwave treatment of the MWCNT (Figure 2 B) with a further decrease of the anodic peak potential of NADH to 0 V caused by the formation of quinone groups at the MWCNT during microwave treatment [40].…”
Section: Sol-gel Ead At Mwcnt Functionalized With Reactive Quinones (mentioning
confidence: 98%
“…For bioencapsulation, the protein is, in principle, simply introduced in the starting sol and is immobilized in the sol-gel thin film formed at the electrode during the gelification process. However, to allow safe encapsulation of sensitive proteins in their active form it is vital to carefully optimize the sol composition [11,18]. Dehydrogenases, which are very sensitive to the sol-gel environment often require the introduction of additive(s), such as positively-charged polyelectrolytes, to preserve their activity in the final electrodeposited matrices [12,19].…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized that silica constitutes a suitable inert matrix for the encapsulation of several biomolecules 11, [46][47][48][49] . However, this material presents a serious drawback from an electrochemical point of view, which is the lack of intrinsic electron conductivity.…”
Section: Introductionmentioning
confidence: 99%